The male dominated field: a study on the gendered experiences of female farmers in northern Colorado - Shisler, Rebecca C., author; Sbicca, Joshua, advisor; Opsal, Tara, committee member; Thilmany, Dawn, committee member (Colorado State University. Libraries, 2016)
This research seeks to understand the gendered experiences of female farm operators in Northern Colorado. Specifically, how do female farmers perceive their experiences through a gendered lens? Semi-structured interviews with sixteen women from Boulder, Larimer, and Weld Counties in the state of Colorado were conducted to explore these experiences. Additionally, a supplementary observation at an agriculture conference was completed to reinforce themes. Analysis revealed that female farmers face many of the challenges faced by women in other male-dominated industries. The data collected through over a dozen interviews revealed that women in agriculture cope with pressures inherent to other male-dominated workspaces, such as coping with tokenism, navigating the double bind, and balancing motherhood with their farmer roles. Additionally, women’s work in agriculture often reflects an ethic of care through engagement with education, feeding others healthful food, and taking care of farmland and the environment.